Propagation Techniques of Endangered Sablot (Litsea glutinosa) Lour. C.B. Rob. - Rabena, Alfredo R. (JPAIR Multidisciplinary Research, 2010)
The Sablot (Litsea glutinosa), a majestic evergreen tree reaching 20-25 meters, boasts fragrant light yellow bark and simple leaves. This research investigated its propagation for conservation purposes. Seed germination thrived best in clay loam soil, achieving a 60% success rate. Interestingly, directly planting stem cuttings proved unsuccessful, but soaking basal cuttings before planting yielded some initial growth. Clay loam again emerged as the superior soil type for overall growth, promoting the greatest height, the most numerous leaves, and the longest leaf length in young Sablot trees. Notably, clay loam nurtured wider young leaves, and while leaf width remained consistent across different soil types, leaf length exhibited significant growth under its influence. These findings highlight the importance of clay loam for successful Sablot cultivation and offer valuable insights for propagating and conserving this remarkable tree.
Keywords: propagation; techniques; sablot; Litsea glutinosa